(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يناقش هذا البحث الأزمة النّفسيّة والاجتماعيّة والسّياسيّة، والفكريّة للإنسان العربيّ في علاقته مع الزّمن من خلال تتبّع الحمولة الإيديولوجيّة التي شحنت بها الأزمنة الرّوائيّة عبر توكيد نزعة هاني الرّاهب الإيديولوجيّة. وعلى الرّغم من الفرص المتاحة لدراسة غير قليلٍ من النّتاج الرّوائيّ العربيّ المعاصر، فإنّ التّنوع الأدائيّ والثّيمي إلى جانب وفرة الأعمال الرّوائيّة، وأهميّة الموقع الذي شغله هاني الرّاهب وما يزال على خارطة الإبداع الرّوائيّ العربيّ؛ شكّل نمطاً من حافزٍ وتحدٍ للخوض في تجربته الرّوائيّة على وجه التّحديد. This research discusses the psychological, social, political and intellectual crisis of the Arab in his relationship with time by tracking the ideological load which was filled up in the narrative times through emphasizing the ideological tendency of Hani Alraheb. In spite of the opportunities to study not a few of the contemporary arabic narrative revenue, the variety in performance and theme along with the abundance of the narrative works and the importance of the site that Hani Alraheb has always held on the arabic narrative creativity map,all of these form a pattern of motivation and challenge to delve into his narrative experience on specific.